A systematic review of the parasites (Plathelminthes: Trematoda) of the Wels catfish (Silurus glanis L., 1758) - Ibrahimova, N. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
The Wels catfish or sheatfish (Silurus glanis L., 1758) is one of the important commercial fishes. Its native range extends from Eastern Europe to Western Asia. Recently, the species range has expanded both to the west and south due to the introduction. In the water bodies of Azerbaijan, the Wels catfish exists at the southernmost border of its range. It was recorded from the Kura River and its basin. There is no survey of parasitological studies on the trematodes of the Wels catfish. The previous papers have not covered all systematic groups or all the areas where the fish is distributed. Based on the literature data, we prepared a systematic review of the Wels catfish trematodes within the catfish present-day range (native area plus the areas of introduction), including Azerbaijan. The list is given according to the system of parasitic organisms implemented in the Catalog of parasites of freshwater fishes of North Asia. We also took into account new studies in the trematode taxonomy. Each species is provided with the following data: synonyms, habitat in the fish body, collecting localities, geographic distribution within the catfish range, infection rates, and references. As a result, 33 trematode species were found in the Wels catfish. They belong to three orders (Aspidogastridea ‒ 1 species, Strigeida ‒ 16 species, and Plagiorchiida ‒ 16 species), 15 families and 24 genera. Of these, 14 species are distributed in the waterbodies of Azerbaijan. The family Diplostomidae (9 species) dominates among the Wels catfish’ trematode parasites. The most Wels catfish trematodes within its whole range are Bucephalus polymorphus, Orientocreadium siluri and Diplostomum spathaceum. We established that Aspidogaster limacoides, Plagioporus skrjabini, Phyllodistomum petruschewskii were recorded from Ukraine only, Allocreadium siluri and Bolboforus confusus, from Uzbekistan, and Asymphylodora kubanica, Bychowskycreadium bychowsky, Bychowskycreadium schiliani, Diplostomum mergi, Diplostomum chromatophorum, and Diplostomum paraspathaceum from Azerbaijan.